Study of Growth and Production of Seven Clones of Sugarcane (Saccharum officinarum L.) Inalluvial Soilin Sambiroto Village, Sooko District-Mojokerto - Miftah Farid Fasheh; Setyo Budi; Wiharyanti Murlailiyah (Nabatia, 2022)
The productivity of sugarcane in Indonesia is still decreasing due to the low value of crystal produced per hectare. One of the main and fundamental factors is the limited availability of superior varieties. The purpose of this study was to determine the differences in growth andyield of clones SB01, SB03 clones, SB04 clones, SB11 clones, SB12 clones, SB19 clones andSB20 clones as well as sugarcane clones that had the best growth. This study used a randomized block design with one factor, namely sugarcane clones SB01, SB3 clones, SB04 clones, SB011 clones, SB12 clones, SB19 clones, SB20 clones. Each replication consisted of 7 sugarcane clones. Which was repeated three times with observation variables which included growth andyield variables. The data were then analyzed using ANOVA variance. If there is a significant difference, continue with the 5% BNT test. There were significant differences between seven sugarcane clones in growth andyield variables in sugarcane. Of the seven clones observed, clone SB12 had good vegetative andgenerative potential with the highestyield of160.67 tons/ha, clone SB01 had the highestyield potential, 11.3% and clone SB01 had the highest crystallizationpotential. namely with a value of 17.6 tons/ha.